2021
DOI: 10.17816/clinpract88180
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of dexmedetomidine in patients with severe COVID-19

Abstract: Rationale: Mortality in patients with severe COVID-19 remains high. Finding therapies that can improve the outcome in these patients is an urgent function. Objective: To evaluate the clinical efficacy of dexmedetomidine in the results of complex treatment with a severe course of COVID-19. Materials and Methods: The retrospective study included 50 adult patients with severe COVID-19 admitted to the intensive care unit (ICU). The primary outcome of the study was the incidence of delirium. The seconda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…Our findings are consistent with other observational studies that found lower mortality with DEX use in critically ill patients with COVID-19 [ 28 , 29 ]. The lower 28-day mortality rate with earlier DEX use relative to IMV is consistent with our previous investigation at Rush University System for Health (RUSH) hospitals [ 28 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings are consistent with other observational studies that found lower mortality with DEX use in critically ill patients with COVID-19 [ 28 , 29 ]. The lower 28-day mortality rate with earlier DEX use relative to IMV is consistent with our previous investigation at Rush University System for Health (RUSH) hospitals [ 28 ].…”
Section: Discussionsupporting
confidence: 93%
“…DEX is reported to improve COVID-19 outcomes including improved oxygen saturation (SpO 2 ) [ 25 ], improved partial pressure of arterial oxygen to the fraction of inspired oxygen (PaO 2 /FiO 2 ) [ 26 ], shortened duration of mechanical ventilation [ 27 ], and reduced mortality [ 28 , 29 ]. However, these investigations have been limited in both scope and size.…”
Section: Introductionmentioning
confidence: 99%